Co-Production Analysis in Waste Management: A Local Perspective - Imam Yudhi Prastya; Ika Riswanti Putranti; Tri Yuniningsih; Budi Puspo Priyadi; Mary Mangai (Journal of Local Government Issues, 2024)
This research aims to analyze co-production practices in waste management through the Waste Bank and Reuse, Reduce, and Recycle Waste Management Area (TPS 3R) in Semarang City on the grounds that Semarang City is the largest waste generate in Central Java Province. Qualitative descriptive was used as a method with data collection techniques using interviews with 11 informants, documentation and observation. Community-based waste management practices are analyzed using the concept of co-production. The findings of this research are that co-production in waste management is motivated by environmental problems, the lack of waste services and government encouragement. Resource sharing occurs between communities, government and Non Government Organizations (NGOs) although the quality of relationships needs to be improved. Waste banks and 3R TPS apart from providing services to residents, is also able to enter "spaces" that the government cannot reach through reducing waste, educating citizens and as a data collector for the government.